Analysis of the Effectiveness of Automatic Lathes Using the OEE and FMEA Methods - Muhammad Bagus Maulana; Dzakiyah Widyaningrum (Advance Sustainable Science Engineering and Technology, 2023)
UD AMJ Jaya Teknik is a manufacturing company that produces various kinds of construction products and spare parts, one of which is boshing products made using an automatic lathe. This research aims to identify the performance of automatic lathe machines to measure the productivity of automatic lathe machines using Overall Equipment Effectiveness and using the Failure Mode and Effect Analysis method. Based on the advantages of OEE, further analysis is carried out to calculate the six big losses. The results obtained from the OEE calculation of 68.22%, this value does not meet the standard ideal OEE value of 85.00%. Meanwhile, the results of the six big loss calculations obtained large values and influenced the effectiveness of the lathe to be minimized, namely process defect loss, reduce speed loss, idling and minor stoppages, and setup and adjustment loss. For the results of the FMEA analysis, the largest RPN value was obtained, namely 336 for the Man factor, with the failure mode that occurred being workers who lacked focus and lack of experience. From the research results of the above calculations, it can be seen that the effectiveness of the UD AMJ Jaya Teknik workshop still needs to be improved, where UD AMJ Jaya Teknik can find out and take corrective action in aspects of machine maintenance and workforce awareness.